Large-scale test of a 3D steel moment-resisting frame with composite slab subject to penultimate interior column loss - Kong, De-Yang; Lyu, Yi-Fan; Dong, Yao-Rong; Wang, Hao; Yang, Yong (Journal of constructional steel research, 2023)
This paper investigates the structural behavior of a typical three-dimensional steel frame-concrete slab substructure (3D composite floor subassembly) subject to a penultimate interior column removal scenario. A two-by-two bay composite floor subassembly is one-third downscaled and quasi-statically pushed down to failure by a specially designed twelve-point loading tree in displacement control mode. Unlike the previous studies where progressive collapse propagates vertically, the current study reveals the possibility of horizontal progressive collapse of 3D composite floor structures that characterized by losing stability of the exterior column. The load-displacement relationships, failure modes, deformation pattern and beam end rotations of the test specimen are presented in detail. Based on the test results, the three load-transferring mechanisms, including flexural action, catenary action and tensile membrane action, are determined and discussed. Besides, the test results are compared with previous test results subject to interior column, edge column and corner column removal scenarios, based on which a structural design and analysis strategy of normal composite buildings against progressive collapse are recommended in this study. •This paper presents a large-scale experimental study on progressive collapse behavior of 3D composite floor subassembly under the penultimate interior column removal scenario;•Flexural action dominates in resisting progressive collapse of 3D composite floor subassembly after losing the penultimate interior column, which contributes by up to 70% of the total resistances;•Tensile membrane action is found to contribute by around 20% - 25% of the total collapse resistances under the penultimate interior column removal scenario;•The exterior column under the penultimate interior column removal scenario is susceptible to failure by losing stability due to the significant second-order effect;•A structural design and analysis strategy is recommended for normal composite buildings against progressive collapse.